2020
DOI: 10.31101/jkk.304
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh jenis persalinan terhadap risiko depresi postpartum pada ibu nifas

Abstract: This study aims to determine the effect of type of delivery onthe risk of postpartum depression in mothers postpartum in hospitalsSleman. This type of research is analytic survey with a retrospective cohortdesign. Hospital research sites in Sleman, Yogyakarta. The population inthis study are all postpartum mothers who visited the poly obstetrics andgynecology in the months from October to December 2015. The totalsample of 110, the data analysis performed univariate and bivariate withchi-square test. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
1
5
0
1
Order By: Relevance
“…Based on the results of the analysis, it was found that there were no confounding variables namely age, education, work, income, social support, and quality of life that were significantly related to postpartum depression. These results are in line with Ariyanti's study that age, parity, education, economic status, family support, and marital status do not significantly influence the risk of postpartum depression (5). The Goker Study (2012) also concluded that there was no significant difference between EPDS scores when compared according to age, education, gravidity, desired pregnancy, fear about birth, sex, family type, and income level (p> 0.05).…”
Section: Methodesupporting
confidence: 82%
See 2 more Smart Citations
“…Based on the results of the analysis, it was found that there were no confounding variables namely age, education, work, income, social support, and quality of life that were significantly related to postpartum depression. These results are in line with Ariyanti's study that age, parity, education, economic status, family support, and marital status do not significantly influence the risk of postpartum depression (5). The Goker Study (2012) also concluded that there was no significant difference between EPDS scores when compared according to age, education, gravidity, desired pregnancy, fear about birth, sex, family type, and income level (p> 0.05).…”
Section: Methodesupporting
confidence: 82%
“…Mothers with cesarean section deliveries are longer healing than vaginal delivery. This will prevent the mother from undergoing her new role as a mother, so that mothers with cesarean delivery are more at risk of postpartum depression, so early detection is needed to see the risk of postpartum depression in postpartum mothers and postpartum mothers at risk of postpartum depression will immediately get treatment (5). The number of respondents who are at risk of postpartum depression is more than double the number of SC deliveries compared to vacuum and spontaneous.…”
Section: Methodementioning
confidence: 99%
See 1 more Smart Citation
“…Pierce (in Kail & Cavanaug, 2000) defines social support as a source of emotional, informational, or assistance from people around individuals who are facing problems and in crisis conditions. This definition is quite similar to Sheeba et al (2019), that social support is an interpersonal interaction that aims to assist someone so that the person feels a form of attention, value, and love (Ariyanti et al, 2016). Therefore, it can be concluded that social support is support or assistance given by the closest person to someone who is facing problems so that they feel a form of attention, are appreciated and become part of the group (Nyfløt et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Mothers with labor complication are at risk of developing postpartum depression (Oktarina, 2016;Ariyanti et al, 2016).…”
mentioning
confidence: 99%